Delineating the molecular landscape of different histopathological growth patterns in colorectal cancer liver metastases - Hu, Mingtao; Chen, Zhigang; Hu, Dandan; Xi, Shaoyan; Wang, Deshen; Zhang, Xiaolong; Fong, William Pat; Wen, Lei; Cai, Yanyu; Yuan, Yunfei; Li, Binkui; Wu, Xiaojun; et al. (Frontiers in Immunology, 2022)
Background Histopathological growth patterns (HGPs) have shown important prognostic values for patients with colorectal cancer liver metastases, but the potential molecular mechanisms remain largely unknown. Methods We performed an exploratory analysis by conducting the RNA sequencing of primary colorectal lesions, colorectal liver metastatic lesions and normal liver tissues. Findings We found that desmoplastic HGPs of the metastatic lesions were significantly enriched in EMT, angiogenesis, stroma, and immune signaling pathways, while replacement HGPs were enriched in metabolism, cell cycle, and DNA damage repair pathways. With the exception of immune-related genes, the differentially expressed genes of the two HGPs from colorectal liver metastases were mostly inherited from the primary tumor. Moreover, normal liver tissue in the desmoplastic HGP subgroup was markedly enriched in the fibrinous inflammation pathway. Conclusions We surmised that HGPs are observable morphological changes resulting from the regulation of molecular expressions, which is the combined effect of the heterogeneity and remodeling of primary tumors seeds and liver soils.